“REFORMAS AL NRAL. 10 DEL ART. 18 DE LA LEY NOTARIAL RESPECTO A LA AUTORIZACIÓN DE LA INSTITUCIÓN INVOLUCRADA PARA EXTINGUIR EL PATRIMONIO FAMILIAR - Lozada Torres, Jonathan Eduardo (2017)
This work is framed in a purely social and legal problem because in our country the law provides that family wealth is constituted on the properties that are awarded by housing schemes, or when they are housing cooperatives, mandated by the Act cooperatives, and are thousands of properties whose domain has been limited by the family estate. At present, many cooperatives have disappeared and even in the Housing Bank in the case of our city; to extinguish the family estate should go to other cities, that is, it creates more of a hassle because you can not cancel the heritage that requires the approval and acceptance of the institution which was the family property, so in the This paper propose the reform of section 10 of Article 18 of the Notary Law, to grant the exclusive power to the notary or notary to attest to the absence of such cooperative or institution involved and without the institution for authorize the extinction of the family patrimony, being immersed in any causal. With this work widely demonstrate the key role that meets or must meet the State, the Constitution of the Republic of Ecuador, the Legislative Branch in due course and other institutions, as is, to ensure the effective implementation of rights people who maintain their homes with family assets, with no beneficiaries and cooperatives or institutions created for social interest housing, no longer exist. It said before involves a series of rights that the state through the Constitution of the Republic of Ecuador, has to secure and ensure the full protection of the right to property to enjoy it without any limitation.